Newly designed primer pair revealed dominant and diverse comammox amoA gene in full-scale wastewater treatment plants - Mingyuan Wang; Guohe Huang; Zhirong Zhao; Dang, Chenyuan; Liu, Wen; Zheng, Maosheng (Bioresource Technology, 2018)
The discovery of complete ammonia oxidizing bacteria (CAOB) capable of performing the two-step nitrification process on their own has fundamentally upended our traditional perception. However, their environmental distribution and ecological significance in driving ammonia oxidation are still urgently awaited to be assessed. In this study, the diversity and abundance of CAOB amoA gene in wastewater treatment plants (WWTPs) were presented taking advantage of a newly designed primer pair specifically targeting CAOB amoA gene. Phylogenetic results demonstrated the novel amoA gene formed a clearly distinct cluster from the canonical amoA and pmoA genes. Among the five well-supported sub-clusters, Nitrospira nitrosa cluster accounted for 94.34% of all the currently retrieved sequences from WWTPs. More importantly, qPCR results demonstrated a remarkably high abundance of CAOB amoA gene, which were up to 182.7-fold more abundant than AOB amoA gene. This study provided new dimension and fundamental basis for future researches towards biogeochemical nitrogen cycle.
Keywords: Abundance; Ammonia oxidation; Comammox; Microbial community; Wastewater treatment